Divorcio y su incidencia en el estado emocional de una mujer de 32 años de edad del cantón Babahoyo - Cevallos Castro, Lady Liliana (2023)
The present case study was developed with the objective of identifying the incidence of divorce in the emotional state of a 32-year-old woman from the Babahoyo canton, having as object of study a woman who is the mother of two children and has a legal divorce process, which began seven months ago. Divorce is a very common process today, many homes have broken up and have gone through this situation, but it is a process that brings negative repercussions on one or more members of the family, mental health is often affected both in the emotional, cognitive and behavioral areas, thus affecting their regular activities, their daily routines, family and social relationships. The divorce has caused the patient to devalue herself, since she lacks personal worth, she feels guilt since she believes she could have done something to avoid what happened, she feels ashamed and afraid of what others will say. The case study has a qualitative and quantitative approach such as direct observation, clinical interview, test and questionnaires with Likert. Strategic activities of a psychotherapeutic nature were carried out, techniques were developed and put into practice from the REBT approach with the aim of providing possible solutions.